GELAR HAJI SEBAGAI STRATIFIKASI SOSIAL PADA MASYARAKAT - Bela Fitri (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2023)
The people of Keboansikep village, Sidoarjo city, which are predominantly Muslim, have mostly gone to hajj and have hajj degrees. The Hajj title for the people in Kebaonsikep is considered to have a role in the social status of the Hajj it has. The purpose of this study was to determine the community's point of view on social stratification in the Hajj title. Data collection techniques used are interviews, observation and documentation. The source of the data for this research is people who see the phenomenon of social stratification in the Hajj title in the village of Keboansikep. This research uses descriptive qualitative data method. The results of this study are that the community is not taboo about this phenomenon, because from generation to generation people who have gone to hajj will get the title of hajj and generally will be in the spotlight in the village, but there are also people's perspectives that are against this phenomenon with their own reasons, so that it raises pros and cons in the community's perspective on Hajj in Keboansikep Village. The status of the pilgrimage has an influence on the social life of the people of Keboansikep Village.